2003
DOI: 10.1038/nature01860
|View full text |Cite
|
Sign up to set email alerts
|

Determining the position of the cell division plane

Abstract: Proper positioning of the cell division plane during mitosis is essential for determining the size and position of the two daughter cells--a critical step during development and cell differentiation. A bipolar microtubule array has been proposed to be a minimum requirement for furrow positioning in mammalian cells, with furrows forming at the site of microtubule plus-end overlap between the spindle poles. Observations in other species have suggested, however, that this may not be true. Here we show, by inducin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
195
1
1

Year Published

2004
2004
2008
2008

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 215 publications
(218 citation statements)
references
References 24 publications
21
195
1
1
Order By: Relevance
“…It has been reported that furrows are formed near the site of high numbers of stabilized microtubules (Canman et al, 2003). We demonstrate that the bundled microtubules lead to accumulation of Rho-mediated signaling molecules and cause ectopic furrowing.…”
Section: Bundled Microtubules Direct Furrow Positioningmentioning
confidence: 79%
“…It has been reported that furrows are formed near the site of high numbers of stabilized microtubules (Canman et al, 2003). We demonstrate that the bundled microtubules lead to accumulation of Rho-mediated signaling molecules and cause ectopic furrowing.…”
Section: Bundled Microtubules Direct Furrow Positioningmentioning
confidence: 79%
“…(59) Further, there is good reason to believe that stable microtubules may somehow signal cytokinetic apparatus establishment. (60) Meanwhile, astral microtubules penetrate the polar cortex in echinoderm embryonic cells sooner and more densely than the equatorial cortex. Treatment of echinoderm blastomeres with low doses of nocodazole results in wider-and sloppier-thannormal Rho zones, which sometimes fail to furrow; likewise, physically restricting access to the cortex by astral microtubules leads to broad, poorly developed Rho activity zones.…”
Section: Transportmentioning
confidence: 99%
“…We also shifted the first furrow using monopolar spindles, as it has been shown that either an isolated aster or a monopolar spindle is sufficient to specify a cleavage plane 4,13 . To generate monopolar spindles, we repeated ASS and subsequently disintegrated the separated aster using the ultraviolet laser ( Fig.…”
Section: Henrik Bringmann 1 and Anthony A Hymanmentioning
confidence: 99%